Positive Association Between Family and Teachers' Tobacco Use on the Smoking Behaviors of Iraqi Adolescents Attending Schools - A Cross Sectional Study Using the Global Youth Tobacco Survey - Fatima Al-Binali; Soha R. Dargham; Ziyad R. Mahfoud (SAGE Publishing, 2024)
Objective: Adolescent tobacco and E-cigarette use have been rising globally in the past decade. Iraq's post-war conflict and economic crises posed psychosocial and mental health trauma, contributing to increased vulnerability to drug and substance use among adolescents. This study looks to assess the potential relationship between current tobacco and E-cigarette smoking and exposure to smoking at home and school among Iraqi adolescents attending schools. Methods: Data analysis for the 2019 Iraq Global Youth Tobacco Survey, a cross-sectional study completed by 2560 Iraqi adolescents aged 11 to 17 years old was conducted. The survey tool which includes demographic, tobacco use, knowledge and attitudes towards tobacco use questions is anonymous and self-administered using paper-based bubble sheets that are scannable. Current tobacco and E-cigarette use (defined as past 30-days) were the main outcomes. Univariate and multivariate logistic regression models were used to assess the relationship between the main outcomes and the following variables: participants' demographics, exposure to smoking, attitude and knowledge scores. Results: Current tobacco and E-cigarette smoking prevalence among Iraqi adolescents attending school were 14.9% (95% CI: 13.5%-16.4%) and 9.7% (95% CI: 8.6%-11.0%), respectively. Exposure to smoking at home was high among fathers (39.1%), mothers (13.9%), siblings smoke (23.9%), other individuals smoke (56.1%). The percentages of students who witnessed people smoking within school premises was 45.7% and observed teachers smoking in schools was 57.6%. The current use of tobacco smoking among Iraqi adolescents was significantly and positively associated with exposure to smoking by the father (AOR = 1.39; 95% CI: 1.05-1.85), mother (AOR = 1.84; 95% CI: 1.30-2.60), sibling (AOR = 3.50; 95% CI: 2.62-4.67), teacher (AOR = 1.48; 95% CI: 1.10-1.98), and people in school (AOR = 1.99; 95% CI: 1.57-2.53). Similarly, the current use of E-cigarettes was significantly associated with father smoking (AOR = 2.02; 95% CI: 1.29-3.16), sibling smoking (AOR = 3.09; 95% CI: 2.04-4.67), and people smoking in school (AOR2.02; 95% CI: 1.39-2.95). Conclusion: Stricter policies need to be enforced to ensure safer school environments that do not expose adolescents to smoking habits of teachers or other students.